ANALISI KEBIJAKAN KURIKULUM PENDIDIKAN AGAMA ISLAM DI MADRASAH: Analisis Keputusan Menteri Agama Nomor 183 Tahun 2019 - rosyid abdur (PASCASARJANA UNISNU, 2022)
Education is a system, so in the work process education must have core components so that it can run as it should. One of the main components of the education system is the content or educational materials. Educational content/materials need to be arranged in such a way as to be called an educational curriculum. The curriculum is a set of plans and arrangements regarding the objectives, content, and learning materials as well as the methods used as guidelines for the implementation of learning activities to achieve the objectives. In formulating the objectives of a curriculum, it must be related to the educational goals to be achieved. In addition, a curriculum compiled or developed cannot be separated from its background and foundations. This article discusses the background and foundations of developing Islamic religious education curriculum in madrasas which are the contents of the Decree of the Minister of Religion Number 183 of 2019. The study was carried out with a content analysis approach regarding the concept or theory stated, then explored more deeply or more broadly to obtain clarity of understanding. The author finds the historical background in the form of challenges that are internal and external to the condition of national education, especially the condition of Islamic religious education in madrasas which is the background for developing Islamic religious education curriculum. Likewise, the existing background contains logical consequences for compiling the foundations of thought as the basics, the footing on which the structure of the Islamic religious education curriculum at the madrasa stands.